Efficient detection technology of DDoS attacks based onBF-DT-CUSUM algorithm in smart grid industrial control system - Jiaxuan FEI; Tao ZHANG; Yuanyuan MA; Cheng ZHOU (Dianxin kexue)
Rapid development of information and communication technology has led China National Grid Corp into the era of intelligent,informational and automated,simultaneously with wide application of information and communication technology in smart grid also providing more ways for attackers to invade and attack power system.A DDoS attacks detection method based on modified CUSUM with dynamic threshold was proposed according to BloomFilter address statistics in smart grid.The proposed method used dynamic threshold technology based on BloomFilter normal traffic statistics,and optimized traditional EWMA algorithm to identify threshold of DDoS attacks,finally modified CUSUM algorithm in order to efficiently detect DDoS attacks in smart grid.Simulation experiments demonstrate that proposed method has high detection speed and precision for DDoS attacks in smart grid,and the system overhead is small.